Multiple Access Techniques for 5G Wireless Networks and Beyond - Vaezi, Mojtaba; Ding, Zhiguo; Poor, H. Vincent (Springer International Publishing : Imprint: Springer, 2019)
This book presents comprehensive coverage of current and emerging multiple access, random access, and waveform design techniques for 5G wireless networks and beyond. A definitive reference for researchers in these fields, the book describes recent research from academia, industry, and standardization bodies. The book is an all-encompassing treatment of these areas addressing orthogonal multiple access and waveform design, non-orthogonal multiple access (NOMA) via power, code, and other domains, and orthogonal, non-orthogonal, and grant-free random access. The book builds its foundations on state of the art research papers, measurements, and experimental results from a variety of sources. Notably, it Includes orthogonal and non-orthogonal waveforms for 5G new radio and beyond: CP-OFDM, UF-OFDM, f-OFDM, WOLA, FBMC, and GFDM; Features NOMA via the power domain (fundamentals, clustering, power allocation, experimental trials, etc.) and the code and other domains (SCMA, IDMA, LDS-CDMA, PDMA, IGMA, RSMA, and RDMA); Outlines random access techniques (CSMA, CSMA/CD, ALOHA, slotted ALOHA, and LoRa), applications and use cases of 5G networks (eMBB, URLLC, mMTC, IoT, and V2V), as well as challenges and future directions in multiple access, random access, and waveform design.